The postprandial rise in plasma cortisol in men is mediated by macronutrient-specific stimulation of adrenal and extra-adrenal cortisol production. - Mohd Shukri, Nor Azwani; Stimson, Roland H.; Bolton, Jennifer L.; Andrew, Ruth; Reynolds, Rebecca M.; Walker, Brian R. (The Endocrine Society, 2014)
Context: Circadian variation is a fundamental characteristic of plasma glucocorticoids, with a postprandial rise in cortisol an important feature. The diurnal rhythm is presumed to reflect alterations in hypothalamic-pituitary- adrenal axis activity; however, cortisol is produced not only by the adrenal glands but also by regeneration from cortisone by the enzyme 11β-hydroxysteroid dehydrogenase type 1, mainly in liver and adipose tissue. Objective: We tested the contribution of peripheral cortisol regeneration to macronutrient-induced circadian variation of plasma cortisol in humans. Design: This was a randomized, single-blinded, crossover study. Setting: The study was conducted at a hospital research facility. Participants: Eight normal-weight healthy men participated in the study. Interventions: Subjects were given isocaloric energy isodense flavor-matched liquid meals composed of carbohydrate, protein, fat, or low-calorie placebo during infusion of the stable isotope tracer 9,11,12,12-[2H]4-cortisol. Outcome Measures and Results: Plasma cortisol increased similarly after all macronutrient meals (by ∼90 nmol/L) compared with placebo. Carbohydrate stimulated adrenal secretion and extraadrenal regeneration of cortisol to a similar degree. Protein and fat meals stimulated adrenal cortisol secretion to a greater degree than extra-adrenal cortisol regeneration. The increase in cortisol production by 11β-hydroxysteroid dehydrogenase type 1 was in proportion to the increase in insulin. The postprandial cortisol rise was not accounted for by decreased cortisol clearance. Conclusions: Food-induced circadian variation in plasma cortisol is mediated by adrenal secretion and extra-adrenal regeneration of cortisol. Given that the latter has the more potent effect on tissue cortisol concentrations and that effects on adrenal and extra-adrenal cortisol production are macronutrient specific, this novel mechanism may contribute to the physiological interplay between insulin and glucocorticoids and the contrasting effects of certain diets on postprandial metabolism